Rapid Discontinuation of Prednisone in Kidney Transplant Recipients: 15-Year Outcomes From the University of Minnesota. Issue 10 (October 2017) - Serrano, Oscar Kenneth; Kandaswamy, Raja; Gillingham, Kristen; Chinnakotla, Srinath; Dunn, Ty B.; Finger, Erik; Payne, William; Ibrahim, Hassan; Kukla, Aleksandra; Spong, Richard; Issa, Naim; Pruett, Timothy L.; et al.
Abstract : Background: Short- and intermediate-term results have been reported after rapid discontinuation of prednisone (RDP) in kidney transplant recipients. Yet there has been residual concern about late graft failure in the absence of maintenance prednisone. Methods: From October 1, 1999, through June 1, 2015, we performed a total of 1553 adult first and second kidney transplants—1021 with a living donor, 532 with a deceased donor—under our RDP protocol. We analyzed the 15-year actuarial overall patient survival (PS), graft survival (GS), death-censored GS (DCGS), and acute rejection–free survival (ARFS) rates for RDP compared with historical controls on maintenance prednisone. Results: For living donor recipients, the actuarial 15-year PS rates were similar between groups. But RDP was associated with increased GS ( P = 0.02) and DCGS ( P = 0.01). For deceased donor recipients, RDP was associated with significantly better PS ( P < 0.01), GS ( P < 0.01) and DCGS ( P < 0.01). There was no difference between groups in the rate of acute or chronic rejection, or in the mean estimated glomerular filtration rate at 15 years. However, RDP-treated recipients had significantly lower rates of avascular necrosis, cytomegalovirus, cataracts, new-onset diabetes after transplant, and cardiac complications. Importantly, for recipients with GS longer than 5 years, there was no difference between groups in subsequent actuarial PS, GS, and DCGS. Conclusions: In summary, at 15 years postkidney transplant, RDP did not lead to decreased in PS or GS, or an increase in graft dysfunction but as associated with reduced complication rates. Abstract : Rapid steroid withdrawal, under the protection of rabbit antilymphocyte induction, leads to fewer complications with no decrease in patient or graft survival or graft function compared to protracted and high dose steroids at 15 years post kidney transplant.